2016
DOI: 10.1016/j.carbon.2016.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamic simulation of layered graphene clusters formation from polyimides under extreme conditions

Abstract: The previous experimental study illustrated that a direct laser scribing on polyimide (PI) induced the layered graphene, which opened a new door of producing graphene associated materials. However, underlain conversion mechanism is unknown, especially from theoretical perspectives. In this paper, we performed the molecular dynamics (MD) simulation of this mechanism under extreme conditions of the high pressure and temperature which mimic the ones generated by the laser induction. We investigated this process u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(105 citation statements)
references
References 35 publications
6
92
0
Order By: Relevance
“…[26] However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high-quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; [39] on the other hand, recent work [40,41] show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.In this study, we investigated in-depth the light-material interaction by developing a reactive MD model to disclose the transient process that leads to LIG formation and identified the critical parameters that govern this process. Following the theoretical prediction, we have experimentally demonstrated that picosecond UV laser processing can also be used to prepare high-quality LIG from PI at ambient conditions.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…[26] However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high-quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; [39] on the other hand, recent work [40,41] show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.In this study, we investigated in-depth the light-material interaction by developing a reactive MD model to disclose the transient process that leads to LIG formation and identified the critical parameters that govern this process. Following the theoretical prediction, we have experimentally demonstrated that picosecond UV laser processing can also be used to prepare high-quality LIG from PI at ambient conditions.…”
supporting
confidence: 81%
“…However, the underlying conversion mechanism for this method is still unclear, and the key parameters to ensure high‐quality graphene are yet to be identified. A molecular dynamics (MD) simulation study by Dong et al suggests that under extreme conditions of high pressure (≈3 GPa) and temperature (>2400 K), which mimic those generated by the infrared laser induction, it is possible to form crystallized layered graphene clusters from PI without the assistance of metal catalysts; this result is consistent with previous experimental observations; on the other hand, recent work show that if UV laser, instead of infrared laser, is used in the conversion process, only very poor quality graphene can be produced, due possibly to the poor absorption of UV light by the carbon source or unoptimized processing conditions.…”
Section: Introductionsupporting
confidence: 69%
“…[8] Therefore, the versatile surface properties of the final carbonaceous materials should be minted during the photothermal reaction and ultrafast cooling. Molecular dynamics (MD) simulation of this direct laser scribing on PI sheets process revealed that extreme conditions of high pressure (≈3 Gp) and high temperature(>2400 K) might be generated by laser induction.…”
Section: Doi: 101002/aelm201800092mentioning
confidence: 99%
“…The entire process can be performed in ambient air without any solvents, thereby making it exceedingly attractive for industrial use. This protocol combines the 3D graphene synthesis with writing into a single step process that has stimulated research ranging from fundamental studies on the transformation process to the development of a large variety of engineering applications …”
Section: Introductionmentioning
confidence: 99%